A new tool for hazard analysis and force-field analysis: The Lovebug diagram. (July 2013) - Card, Alan J
Background: Fishbone diagrams have been widely promoted as a systems-focused hazard analysis tool for use in root cause analysis, but they suffer from a number of structural weaknesses, including a unidirectional structure that only takes into account forces that promote an accident (ignoring those that make the accident less likely or less severe) and a means of displaying these forces that does not convey any difference in strength of influence. In a separate but related issue, many healthcare organizations suffer from a lack of change management expertise. Proposed solution: To address these concerns, I present a novel technique, the Lovebug diagram, which draws from both Fishbone diagrams and force-field analysis (an approach to analyzing planned change). This new technique adds value to both its progenitor methods, while retaining their key strengths and ease of use. It can be used both prospectively, to assess planned changes, and retrospectively to assess unplanned (accidental) departures from the status quo. Discussion: The Lovebug diagram is a more powerful analytical tool than its progenitor methods; however, overall adoption of systems-focused tools for root cause analysis remains suboptimal. Additional research is needed to determine how best to promote a truly systems-focused approach to healthcare root cause analysis. Beyond this retrospective use of the technique, it represents a simple tool to assist healthcare organizations with prospective change management.